Rise of the wolf - Nielsen, Jennifer A. (New York : Scholastic Press, 2016)
Now a driver in the chariot races, Nic is still a target of the Praetors because of the magical amulet he found, and they will do anything to get their hands on it--and meanwhile Atroxia is beginning to wake up.
800-899
Keywords: Magic -- Juvenile fiction; Amulets -- Juvenile fiction; Conspiracies -- Juvenile fiction; Dragons -- Juvenile fiction; Chariot racing -- Juvenile fiction; Magic -- Fiction; Amulets -- Fiction; Conspiracies -- Fiction; Dragons -- Fiction; Chariot racing -- Fiction; Rome -- Antiquities -- Juvenile fiction; Rome -- History |y Empire, 30 B.C.-476 A.D. -- Juvenile fiction; Rome -- History |y Empire, 30 B.C.-476 A.D. -- Fiction